The value of political connections in the first German democracy: Evidence from the Berlin stock exchange - Sibylle Lehmann-Hasemeyer; Alexander Opitz (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
In this paper, we provide the first overview over all political connections for all firms listed on the Berlin stock exchange in 1924 and for the same sample of firms four years later. In contrast to anecdotal evidence which suggest that these political connections had a positive effect on firms' performance, an event study based on the election in December 1924 and May 1928 shows only little evidence that political connections had a positive impact on firm value. These results complement previous research emphasizing that political connections might have mattered less in democracies. Indeed, this seems true for Germany's first democracy - even though it was a very unstable one.
urn:nbn:de:bsz:100-opus-14088
Keywords: 330; Political Connections; Interwar Germany; Stock Market Performance